Using Google Classroom in Biology Class and the Effect on Senior High School Students Motivation and Learning Outcome - Agustina, Putri; Hafizh, Muhammad; Rahmawati, Arik; Arfian, Muhammad; Wijayanti, Ismi Puji (Universitas Muhammadiyah Surakarta, 2024)
Industrial Revolution 4.0 causes changes in various fields, including education. One of the changes in the education sector is the integration of technology into the learning process. One of the integrations of technology in learning is the use of a Learning Management System (LMS). Google Classroom is one LMS choice that can be used for learning. This research aims to analyse the effectiveness of using Google Classroom on students' motivation and learning outcomes in Biology. This research is a pre-experimental research with a one-group pre-test and post-test research design. This research was conducted in 4 senior high school in Central Java namely SMA MTA Surakarta, SMA PGRI 1 Pati, MAN 1 Grobogan, and SMA Negeri 2 Mranggen. This research was carried out during the 2021/2022 academic year. Data collection techniques include questionnaires, tests, and observation instruments. This research sample consists of 184 students of XI grades. Each class is given treatment using Google Classroom. Based on the results of the research and discussion, conclusions can be drawn: (1) Learning using Google Classroom can have a positive impact on student learning motivation, as can be seen from the average motivation score of 77.47; (2) Learning using Google Classroom is effective for student learning outcomes in the medium effectiveness category (average N-Gain score 43.77).